Tannic complexes coated nanocontainers for controlled release of corrosion inhibitors in self-healing coatings. (20th February 2019) - Qian, Bei; Michailidis, Marios; Bilton, Matt; Hobson, Theo; Zheng, Zhaoliang; Shchukin, Dmitry
Abstract: Nanocontainers with controlled release properties have been used in self-healing coatings for many years. However, the spontaneous leakage of the small molecular weight inhibitors from the nanocontainers promoted the development of nanovalves or gatekeepers to control inhibitor release. Herein, we demonstrate a facile method to encapsulate corrosion inhibitor in mesoporous silica nanoparticles (MSNs) with the help of tannic acid complexes, which endow the inhibitor loaded MSNs with pH-controlled release function. Commercial water-borne alkyd coating impregnated with 2 wt% of benzotriazole-loaded nanocontainers presented significant self-healing effect after 20 days of immersion in 0.1 M NaCl solution from both released benzotriazole and tannic acid as confirmed by electrochemical impedance spectroscopy and microscopy. The impedance modulus of coating with nanocontainers increased from 4.7 × 10 4  Ω cm 2 to 1.8 × 10 5  Ω cm 2 after 15 days of immersion. Highlights: Autonomic self-healing coatings for corrosion protection. Inhibitor-loaded nanocontainers with dual self-healing effect. Mesoporous silica nanoparticles as nanocontainer hosts. Attaining self-healing properties to water-borne alkyd paints. Controlled release of encapsulated inhibitor by tannic-Fe (III) complex.